2011
DOI: 10.1073/pnas.1113877108
|View full text |Cite
|
Sign up to set email alerts
|

Complex genetic architecture of Drosophila aggressive behavior

Abstract: Epistasis and pleiotropy feature prominently in the genetic architecture of quantitative traits but are difficult to assess in outbred populations. We performed a diallel cross among coisogenic Drosophila P-element mutations associated with hyperaggressive behavior and showed extensive epistatic and pleiotropic effects on aggression, brain morphology, and genome-wide transcript abundance in head tissues. Epistatic interactions were often of greater magnitude than homozygous effects, and the topology of epistat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
68
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 45 publications
4
68
0
Order By: Relevance
“…The effects of Drosophila mutations (33) and natural variants (37) on aggression depend on genetic background, a phenomenon also observed for mutations in neuronal nitric oxide synthase (38) and Nr2e1 (16) in mice. Analysis of naturally segregating variation can leverage polymorphisms at many loci to explore the contribution of epistatic interactions to genetic variation for complex traits (39)(40)(41).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of Drosophila mutations (33) and natural variants (37) on aggression depend on genetic background, a phenomenon also observed for mutations in neuronal nitric oxide synthase (38) and Nr2e1 (16) in mice. Analysis of naturally segregating variation can leverage polymorphisms at many loci to explore the contribution of epistatic interactions to genetic variation for complex traits (39)(40)(41).…”
mentioning
confidence: 99%
“…The cuticular hydrocarbon (z)-7-tricosene is also required for male−male aggression; this effect is modulated via gustatory receptor neurons expressing Gr32a (30). Unbiased mutagenesis screens for genes affecting aggressive behavior (31) and transcriptional profiling of mutations (32,33), artificial selection lines (34,35), and wild-derived inbred lines (36) divergent for aggressive behavior have implicated hundreds of genes spanning diverse biological processes.…”
mentioning
confidence: 99%
“…Cost-effective epigenetic and physiological models are needed for (i) addressing tissue-specific responses to toxins, (ii) gaining insights into mechanisms of epigenetic toxicity, and (iii) evaluating the manifestation of these responses across naturally occurring genotypes. In particular, cost-effective models with massive publicly available genetic information (Zwarts et al 2011;King et al 2012a,b;Mackay et al 2012) might allow for genome-wide evaluation of toxic responses and assessment of coexposure outcomes in conjunction with the evaluation of unique individual responses.…”
mentioning
confidence: 99%
“…Indeed, a recent study identified up-and downregulation of more than 4,038 genes in differences in aggression in fruit flies (Zwarts et al 2011). It is not sufficient, however, to pay lip service to the existence of such extreme polygenicity and environmental interaction and then defend the plausibility of resultsthat a single polymorphism can predict a behavior such as voter turnout-that directly contradict those same principles.…”
Section: Responses To a Few Objectionsmentioning
confidence: 99%